Purification and characterization of Bacillus cereus protease suitable for detergent industry - Prakash M.; Banik R.M.; Koch-Brandt C. (My University, 2025)
An extracellular alkaline protease from an alkalophilic bacterium, Bacillus cereus, was produced in a large amount by the method of extractive fermentation. The protease is thermostable, pH tolerant, and compatible with commercial laundry detergents. The protease purified and characterized in this study was found to be superior to endogenous protease already present in commercial laundry detergents. The enzyme was purified to homogeneity by ammonium sulfate precipitation, concentration by ultrafiltration, anion-exchange chromatography, and gel filtration. The purified enzyme had a specific activity of 3256.05 U/mg and was found to be a monomeric protein with a molecular mass of 28 and 31 kDa, as estimated by sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE) and nondenaturing PAGE, respectively. Its maximum protease activity against casein was found to be at pH 10.5 arid 50°C. Proteolytic activity of the enzyme was detected by casein and gelatin zymography, which gave a very clear protease activity zone on gel that corresponded to the band obtained on SDS-PAGE and non-denaturing PAGE with a molecular mass of nearly 31 kDa. The purified enzyme was analyzed through matrix-assisted laser desorption ionization-time-of-flight-mass spectrometry (MALDI-TOF-MS) and identified as a subtilisin class of protease. Specific serine protease inhibitors, suggesting the presence of serine residues at the active site, inhibited the enzyme significantly. Copyright © 2005 by Humana Press Inc. All rights of any nature whatsoever reserved.